Influence of water sorption on the shrinkage stresses of dental composites - Domarecka, Monika; Sokołowski, Krzysztof; Krasowski, Michał; Szczesio, Agata; Bociong, Kinga; Sokołowski, Jerzy; Łukomska-Szymańska, Monika (Journal of Stomatology, 2016)
Introduction. The elimination or reduction of shrinkage stress generated during polymerisation is one of the major problems in the development of dental composites. Sorption of water by resin fillings in the moist environment of the oral cavity and in consequence its volume expansion should counteract the observed shrinkage contraction. Aim of the study. To evaluate the influence of water sorption in resinbased materials on polymerization shrinkage stress generated on the restoration-tooth interface. Material and methods. The shrinkage stress was measured immediately after curing. The samples stored in water were evaluated after 24 h for 7 days and then once a week up to 90 days. Photoelastic study was performed on photosensitive epoxy resin plates in Transmission Polariscope FL200. The study was based on the analysis of dimension and arrangement of fringes. Contraction stress was calculated on the basis of photoelastic theory. In order to measure the water sorption and its dynamics, the material samples were weighed on analytical scale in the above mentioned time intervals. Results. The tested materials during polymerization generated shrinkage stresses ranging